A totally new automation platform for current and future mining machine automation (The Southern African Institute of Mining and Metallurgy, 2001)
Now a new generation of computerized drill rigs has been launched and they are based on modern standard PC-computer technology. The rigs have been well embraced by the market and more than 100 units have left the assembly line. The new generation has taken a quantum leap forward with respect to drilling accuracy, logging capabilities, reduction of manpower in some types and serviceability compared to the previous generation of drill rigs. The Can bus technology, well proven in the automobile products, is the backbone in the new generation control system of Atlas Copco. The short-term development is now focused on establishing this new automation platform on other product lines of Atlas Copco products. The long-term objectives is to offer the mining industry Atlas Copco products with one common automation platform. Essential for Atlas Copcois to contribute to the work with the on-going Data Exchange standard between mining machines and mining computer systems (IREDES). Our belief is that an accepted standard will make mine automation programs affordable for a wider base of the mining industry, because of the possibilities to a cost effective integration of different equipment with a minimum of system integration problems and machine specific interfaces.